Programming Languages and Systems - Ramalingam, G. (6th Asian Symposium, APLAS, 2008)
This volume contains the proceedings of the 6th Asian Symposium on Programming Languages and Systems (APLAS 2008), which took place in Bangalore, December 9–December 11, 2008. The symposium was sponsored by the Asian Association for Foundation of Software (AAFS) and the Indian Institute of Science. It was held at the Indian Institute of Science, as part of the institute's centenary celebrations, and was co-located with FSTTCS (Foundations of Software Technology and Theoretical Computer Science) 2008